EP1215 Postoperative radiotherapy does not benefit stage IB-IIA cervical squamous cell carcinoma with intermediate risk according to sedlis criteria. (1st November 2019) - Cao, L; Wen, H; Feng, Z; Han, X; Wu, X
Abstract : Introduction/Background: Postoperative radiotherapy was proved to reduce recurrence of intermediate-risk stage IB cervical cancer by GOG 92 trial initiated in 1988.This study was aimed to demonstrate whether postoperative radiotherapy (w/o concurrent chemotherapy) influences the outcomes of early-stage cervical squamous cell carcinoma with intermediate risk in the current background. Methodology: Patients with stage IB1-IIA2 (FIGO 2009) cervical squamous cell carcinoma who underwent radical hysterectomy and pelvic lymph node dissection at our institution between March 2006 and February 2014 were reviewed. Only patients with no positive lymph nodes, surgical margin or parametrium but with intermediate-risk factors according to Sedlis criteria were included. Patients who underwent observation (Obs.), radiotherapy alone (RT) and radiotherapy with concurrent chemotherapy (CCRT) postoperatively were compared for recurrence-free survival (RFS), disease-specific survival (DSS), and site of first relapse (pelvic vs distant vs combined pelvic and distant). Results: 94 patients in Obs. group, 279 patients in RT group and 488 patients in CCRT group were included. Five-year RFS were 84.8%, 84.5% and 89.9% for Obs., RT and CCRT group, respectively ( p =0.22).Corresponding five-year DSS were 90.7%, 88.0% and 91.5%, respectively ( p =0.21). Adjuvant radiotherapy (w/o concurrent chemotherapy) was not an independent prognostic factor for RFS and DSS compared with no further treatment (all p >0.05). There was no significant difference in the distribution of site of first relapse among three groups ( p >0.05). Among entities of Sedlis criteria, patients with combination of positive lymph vascular space invasion (LVSI) and deep 1/3 stromal invasion had much poorer RFS ( p =0.02) and DSS ( p =0.004) compared with those with combination of negative LVSI, middle or deep 1/3 stromal invasion and tumor diameter ≥ 4cm. Conclusion: Postoperative radiotherapy (w/o concurrent chemotherapy) doesn't benefit patients with intermediate risk according to Sedlis criteria. The prognosis of patients meeting Sedlis criteria is not even balanced. Disclosure: Nothing to disclose.